Continuous infusion versus intermittent dosing of ceftazidime/avibactam in critically ill patients with Klebsiella pneumoniae OXA-48 or Pseudomonas aeruginosa infections: a single-center randomized open-label trial (ZAVICONT). Rationale and design - Momčilović, Mirna; Šitum, Ivan; Erceg, Ante; Siroglavić, Marko; Lovrić, Mila; Nižić Nodilo, Laura; Hafner, Anita; Lovrić, Jasmina; Turčić, Petra; Fabijanović, Dora; Marinić, Ana; Nedeljković, Vanja; et al. (Frontiers in Pharmacology, 2025)
ObjectiveCeftazidime/avibactam (CZA) is an essential treatment option for managing infections caused by multidrug-resistant (MDR) Gram-negative (G−) bacteria, including Klebsiella pneumoniae OXA-48 and carbapenem-resistant Pseudomonas aeruginosa. Growing evidence indicates that critically ill intensive care unit (ICU) patients often exhibit altered pharmacokinetics (PK) of CZA, which may compromise the achievement of optimal PK/pharmacodynamic (PD) targets with standard dosing regimens. The primary hypothesis of this study is that continuous infusion (CI) of CZA improves microbiological success compared to intermittent dosing (ID) in critically ill ICU patients with severe infections caused by K. pneumoniae OXA-48 or P. aeruginosa.MethodsThis is a single-center, randomized, open-label trial with a 1:1 allocation ratio, conducted at the University Hospital Centre Zagreb, a tertiary care hospital in Croatia. A total of 140 critically ill ICU patients with severe infections due to K. pneumoniae OXA-48 or P. aeruginosa requiring CZA treatment will be randomized to receive either ID of CZA (2 g/0.5 g/8 h over 2 h) or the same total daily dose in CI (6 g/1.5 g over 24 h). The study is powered to demonstrate the superiority of CI over ID of CZA in terms of microbiological success.OutcomesThe primary outcome will be microbiological success rate, chosen as a key indicator of pathogen eradication that is directly influenced by PK/PD target attainment. Secondary outcomes will include clinical success rate, time to symptoms improvement, length of ICU stay, length of hospital stay, all-cause 28-day mortality, pathogen recurrence rate on day 28, time to weaning from mechanical ventilation, cumulative vasoactive-inotropic score, adverse events, and the ratio of ceftazidime plasma concentration to the pathogen’s minimum inhibitory concentration (C/MIC).ConclusionThis trial will provide evidence on optimal CZA administration regimen in critically ill ICU patients with severe infections due to MDR G-pathogens.Clinica Trial Registrationclinicaltrials.gov, identifier NCT06811727.